Real-life experience with chlormethine gel for early-stage mycosis fungoides with emphasis on types and management of cutaneous side-effects#. (19th May 2022) - Prag Naveh, Hadas; Amitay-Laish, Iris; Zidan, Omri; Leshem, Yael A.; Sherman, Shany; Noyman, Yehonatan; Taieb, Joseph; Didkovsky, Elena; Hodak, Emmilia
Abstract: Background: Real-life efficacy data on the recently approved once daily application of chlormethine gel (CG) for mycosis fungoides (MF) is limited, and detailed characterization of the side effects and their management are strikingly sparse. Objective: To evaluate the efficacy and particularly the side effect profile of CG in early-stage MF patients in a real-life setting. Methods: We performed a single-center retrospective analysis of 66 early-stage MF adult patients treated with CG in 2016–2019. Results: Treatment with a once-daily application (52%), or at lower frequencies (48%), in some with topical corticosteroids (TCS) (40%), resulted in an overall response rate of 50%, with no significant difference between stage IA and IB. Cutaneous side effects (56%) included irritant or allergic contact dermatitis (36%, mostly mild/moderate and manageable by reducing application frequency and/or adding TCS or interrupting treatment), unmasking effect (9%), hyperpigmentation (14%), and pruritus (9%). Withdrawal due to side effects occurred in 19.6% of patients (15% for contact dermatitis). Conclusion: In real-life management, flexible regimens of CG sometimes with TCS, show efficacy in early-stage MF and may reduce the rate of contact dermatitis, the main treatment-limiting side effect. Practical recommendations with emphasis of the types, time of appearance, and management of side effects are provided.